Relations between the deposits means and the chemical trials in the Samacá Coal - Suescún-Torres, Jaime Humberto (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2007)
This is a base for a broader regional study, which comprises the geologic cartgraphy, caracterization and calculation of reserves for coals pertaining to the level Ktg-2-Ktg-3 of the Guaduas Formation. The intention was to establish the relation betwen the chemical analysis and the deposit en enviroment, by comparing the strata-graphic columns with the curves of the chemical tests. After describing the strata-graphic column from the lito-logical point of view there were taken samples of the carboniferous mantles  levels for further petro-grahhic trials. Finally to make comparisons with the enviroment deposits by means of tables and graphics. From the comparative graphs it is deduced that as the environment become morecontinental, it increases the contents of vitrinite and power of reflectance diminish. It is recommended to carry on studying on a greater number of samples that include the other studies already made.